The Role Of The Teacher In Curriculum Development Islamic Education At Smps Islamic Assirojiyah Omben Sampang - Marsuki Fadli; Lusi Dian Nur Faiq; Buna'i Buna'i (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Abstract: educators have duties and responsibilities for the learning process by conveying knowledge and various beliefs to students so that they implement their knowledge in everyday life. The success of the learning process can be seen from the applied curriculum, the curriculum has two sides, namely as a document and as an implementation. From the problems above, the researcher interpreted and created a title